HOTELS ADVERTISEMENTS ON INSTAGRAM DURING COVID-19 PANDEMIC: A CRITICAL DISCOURSE ANALYSIS (Iklan Perhotelan di Instagram pada Masa Pandemi Covid-19: Analisis Wacana) - K.M. Tri Sutrisna Agustia (Sirok Bastra, 2021)
This paper aimed at investigating the use of the advertisement text in Instagram caption of hotels during the Covid-19 pandemic. The paper is analyzed under the three dimensions of Critical Discourse Analysis theory proposed by Fairclough (1989). The descriptive qualitative approach used to obtain and explain the secondary data. The result of description dimension showed: the used of significant meaning, active-passive sentences, positive-negative sentences, and description-persuasion structures. The interpretation dimension showed that the content, subject, relations, and connections were referred to as the situational context. The explanation dimension showed, the relation of situational, institutional, and social contexts. Tulisan ini bertujuan untuk mengetahui penggunaan teks iklan pada takarir Instagram di hotel-hotel selama masa pandemi Covid-19. Tulisan ini dianalisis dengan teori tiga dimensi analisis wacana kritis yang diajukan oleh Fairclough pada tahun 1989. Pendekatan deskriptif kualitatif digunakan untuk memperoleh dan menjelaskan data sekunder. Hasil dari dimensi deskripsi menunjukkan bahwa penggunaan makna signifikan, kalimat aktif-pasif, kalimat positif-negatif, dan struktur deskripsi-persuasi. Dimensi interpretasi menunjukkan bahwa isi, subjek, hubungan, dan koneksi mengacu kepada konteks situasional. Dimensi penjelasan menunjukkan bahwa hubungan pada konteks situasional, kelembagaan, dan praktik sosial.